2017
DOI: 10.1007/s10534-017-0027-9
|View full text |Cite
|
Sign up to set email alerts
|

Chromium(III) and iron(III) inhibits replication of DNA and RNA viruses

Abstract: The aim of this study was to examine the effect of treating of chromium(III) and iron(III) and their combinations on Herpes Simplex Virus type 1 (HSV-1) and Bovine Viral Diarrhoea virus (BVDV) replication. The antiviral efficacies of chromium(III) and iron(III) on HSV-1 and BVDV were evaluated using Real Time PCR method. Moreover, the cytotoxicity of these microelements was examined using the MTT reduction assay. The IC50 (50% inhibiotory concentration) for the chromium chloride was 1100 μM for Hep-2 cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 23 publications
(41 reference statements)
0
11
0
1
Order By: Relevance
“…Among the heavy metal ions, chromium (III) ion has great impacts on the various systems such as chemical, biological and environmental systems. It is a crucial trace element in human nutrition to balance the "glucose tolerance factor" [1] and also acts as an essential role in the metabolism of proteins, nucleic acids, carbohydrates, and fats [2,3]. The National Research Council of United State has highly recommended taking 50-200 µg d −1 as an important amount of chromium (III) ion.…”
Section: Introductionmentioning
confidence: 99%
“…Among the heavy metal ions, chromium (III) ion has great impacts on the various systems such as chemical, biological and environmental systems. It is a crucial trace element in human nutrition to balance the "glucose tolerance factor" [1] and also acts as an essential role in the metabolism of proteins, nucleic acids, carbohydrates, and fats [2,3]. The National Research Council of United State has highly recommended taking 50-200 µg d −1 as an important amount of chromium (III) ion.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the natural adsorbents, including clay, charcoal, and clay minerals showed 99.99% adsorption of CoVs ( Robson, 2020 ). Some minerals that may act against CoVs are selenium ( Ma et al., 2019 ), copper ( Rupp et al., 2017 ), iron ( Jayaweera et al., 2019 ), chromium ( Terpiłowska and Siwicki, 2017 ), potassium ( Punch et al., 2018 ), zinc ( Te Velthuis et al., 2010 ), and so on. Moreover, medicinal plants or their derivatives are also evident to act against hCoVs ( Kim et al., 2010 ; Aanouz et al., 2020 ; Islam et al., 2020 ).…”
Section: Discussion: Challenges and Clinical Perspectives On Covid-19mentioning
confidence: 99%
“…The metal ions are expected to be involved in sterilization. Several studies have reported that iron chloride exhibits antiviral activity in a concentration-dependent manner against herpes simplex virus type 1 (HSV-1) and bovine viral diarrhea virus and decreases the number of RNA or DNA replicates 16 . Zinc was shown to play a complementary role in enhancing bactericidal activity against the common mastitis causative pathogens Streptococcus uberis , S. aureus , and E. coli.…”
Section: Discussionmentioning
confidence: 99%